Effects of Certolizumab on Cerulein-Induced Acute Pancreatitis in Rats. Issue 8 (September 2016) - Kosekli, Mehmet Ali; Sungurtekin, Ugur; Cobankara, Veli; Ozmen, Ozlem; Sahinduran, Sima; Yilmaz, Mustafa
Abstract : Objectives: To evaluate the effects of certolizumab, a pegylated monoclonal antibody to tumor necrosis factor α (TNF-α), on experimentally induced acute pancreatitis. Methods: Healthy Wistar Albino male rats (n = 36) were randomly divided into 4 groups (9 rats in each group): group 1, control group; group 2, certolizumab group; group 3, cerulein group; and group 4, cerulein + certolizumab group. Acute edematous pancreatitis was induced via intraperitoneal injection of 80-μg/kg cerulein (20 μg/kg, 4 times at 1-hour intervals) in groups 3 and 4. Certolizumab (10 μg) was intraperitoneally administered in groups 2 and 4. Serum levels of amylase, lipase, TNF-α, and lactate dehydrogenase were evaluated. Histopathology and immunohistochemistry of the pancreatic tissue for assessing the activities of malondialdehyde, myeloperoxidase, TNF-α, and caspase-3 were also performed after 72 hours. Results: Certolizumab treatment significantly decreased the serum levels of amylase, lipase, and lactate dehydrogenase. Histopathological edema, hemorrhage, parenchymal necrosis, and infiltration scores were also decreased, along with a decrease in malondialdehyde, myeloperoxidase, TNF-α, and caspase-3 activities. Conclusion: This study suggests that certolizumab is a beneficial treatment mode for reducing the severity of acute pancreatitis.